2015
DOI: 10.5599/admet.2.4.130
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Transdermal Delivery of Benfotiamine in an Animal Model

Abstract: We designed a transdermal system to serve as a delivery platform for benfotiamine utilizing the attributes of passive penetration enhancing molecules to penetrate through the outer layers of skin combined with the advance of incorporating various peripherally-acting vasodilators to enhance drug uptake. Benfotiamine, incorporated into this transdermal formulation, was applied to skin in an animal model in order to determine the ability to deliver this thiamine pro-drug effectively to the sub-epithelial layers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…3C and D). As shown in many studies, [9][10][11][12] these analogs easily diffuse across plasma membranes leading to increases in intracellular thiamine levels. Therefore, this result suggested that the thiamine analogs were converted into thiamine aer crossing the cell membrane.…”
Section: Application Of the Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…3C and D). As shown in many studies, [9][10][11][12] these analogs easily diffuse across plasma membranes leading to increases in intracellular thiamine levels. Therefore, this result suggested that the thiamine analogs were converted into thiamine aer crossing the cell membrane.…”
Section: Application Of the Methodsmentioning
confidence: 87%
“…Benfotiamine and sulbutiamine have excellent bioavailability [5][6][7][8]10,11 and are known to easily cross cell membranes and increase intracellular thiamine levels. [9][10][11][12] Benfotiamine, an S-acyl derivate of thiamine, was discovered to stimulate transketolase (TKT) activity involved in glucose metabolism and prevent diabetic nephropathy in a similar manner to high-dose thiamine. [13][14][15] Sulbutiamine, a dimer of two modied thiamine molecules, is widely used clinically as a treatment for brain function including memory disorders and asthenia.…”
Section: Introductionmentioning
confidence: 99%